Perceived stress among nurses of psychiatric ward patients with and without suicidal behavior - Haider, Ali; Masroor, Uzma (International Journal of Advanced Nursing Studies, 2017)
Background and Objectives: The present research was conducted to obtain a perceived stress pattern among nurses attending the psychiatric patients with suicidal and non-suicidal behavior in the different hospitals and clinics of the twin- cities (Islamabad and Rawalpindi) of Pakistan. The main objective of the study was to have an idea about the environment of nursing in psychiatric wards in Pakistani culture.Participants and Method: The sample (N= 36) comprised of the nurses of psychiatric ward attending the one patient for 12 hours (n=16) with and (n=20) without suicidal behavior working into night and day shifts respectively. All the participants gave responses on the perceived stress scale. Participants were approached during their duty hours and were given perceived stress scale 10- items along with demographic information sheet and the consent form. Between group-design was used in the present study.Results and Conclusion: The results indicated that verification of both hypotheses, i.e. the nurses of patients with suicidal behavior had more perceived stress (M= 42 Â±3.5) than the nurses of patients without suicidal behavior (M= 19.11 Â± 5.7) and also the old nurses had a greater level of perceived stress than the younger nurses according to the same statistics. The t- test, t (28.5) = 14.9 p< 0.05 was significant on 95% confidence interval with variance not equal. Limitations and suggestions for future were also discussed. Both the hypotheses were supported by the analysis- results and by the previous literature.